The Effect of Student Personality Development on Educator Performance in Indonesian Schools - H. Asep Idrus Alaw (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Teachers are the pillars of the development of society's building blocks, i.e., the students; therefore, for the effective and constructive nourishment of the students, the performance of the teachers must be excellent with the support of external elements. To empirically analyse teachers' performance, this study employed a quantitative research technique, elucidating the influence of school environment, character development, and school administration on teachers' performance levels through the mediation of the efficacy component of individual personality. The study targeted high school teachers in Indonesia, collected data purposefully using a survey instrument, and used a total of 227 legitimate and effective responses to compile the results. The research found substantial results for all direct interactions, and mediation was recommended for the school climate and teacher performance. The study added a fresh piece of evidence to the literature by shedding light on the impact of external environmental elements at the school level on teachers' performance.